Pemanfaatan Sistem Informasi Marketplace Go Market untuk UMKM di Kota Batam Bekerjasama dengan PT Pundi Mas Berjaya - Prasetyo, Stefanus Eko; Basri, Germen (Jurnal Tiyasadarma, 2024)
The utilization of marketplace platforms is becoming increasingly popular and effective in the era of digitalization, helping SMEs to enhance their marketing focus and product sales. Marketplaces provide opportunities for business actors to expand their market reach and increase sales. The design and development of the marketplace information system named Go Market aims to assist PT Pundi Mas Berjaya in providing software solutions for the SME market. The development method for the Go Market application involves stages of Planning, Analysis, Design, Implementation, and Testing. The implementation schedule runs from January to May. The creation of the Marketplace, system implementation, and system testing are conducted in collaboration with PT Pundi Mas Berjaya. The results include the development of the Go Market application using the Laravel framework, which can be used to expand the SME market. The implementation of the marketplace system involves user-side and admin features, along with system testing to ensure optimal performance. The application's backend operates well, providing an efficient solution for data processing, with hopes for continuous development in the future. The output takes the form of an application that will be utilized by PT Pundi Mas Berjaya in enhancing users' understanding and skills in leveraging technology for SMEs. This project successfully developed the Go Market application with a well-functioning backend. All functionalities can assist users in processing sales data more efficiently.